Faktor Aging Population di Jepang dan Upaya Pemerintah Jepang dalam Mengatasi Fenomena Tersebut - Eryano, Mochamad Bintang Putra; Insani, Nurul Amaliah; Parasati, Yafi Annisa; Wardhani, Dyah Lukita; Anwari, Khoirul Rizal; Ayyub, Ichlasul (Sabda: Jurnal Kajian Kebudayaan, 2023)
Aging population is an issue that is quite worrying in Japan. From year to year the population birth graph continues to decline combined with life expectancy which causes Japan's population to age very quickly. This research tries to discuss the relationship between the factors that influence the aging population, accompanied by solutions carried out by the Japanese government to overcome the aging population. This research aims to describe the causes of the aging population and what the government's strategy is to overcome this. This research is a qualitative research. Data sources include scientific articles and reports from Japanese government agencies that discuss the aging population. The discussion is carried out by identifying problems using a social change theory approach. The results of the analysis show that the aging population phenomenon in Japan is caused by decreasing birth rates, urbanization, changes in modern lifestyles, and traditional gender roles. The Japanese government has implemented several things in response to this problem. However, this challenge requires cross-sector collaboration to create an environment that supports child birth and child growth.